The Relationship Of The Duration Of Gadget Use With The Emotional Intelligence Of Adolescents In SMA Negeri 1 Binjai Langkat District - Mona Fitri Gurusinga; Afrilius Simanjuntak; meta Hutagalung; Siti Marlina (Jurnal Pengabdian Masyarakat Putri Hijau, 2023)
In this era of globalization, many teenagers are affected by technological advances, one of the technologies that teenagers enjoy is gadgets. Gadgets have an appeal to teenagers where gadgets can be used to fill various applications. However, excessive use of gadgets in adolescents can make teenagers not care about the environment, so that it can affect the ability to empathize, express emotions appropriately, manage emotions, and all of these are aspects of emotional intelligence. The purpose of this study was to determine the relationship between the duration of gadget use and adolescent emotional intelligence in SMA Negeri 1 Binjai, Langkat Regency. This type of research is correlational with a cross sectional approach. The population in this study was 280 10th grade students at SMA Negeri 1 Binjai Langkat Regency, the sample size used was 74 respondents. The sampling technique used is simple random sampling. Methods of data collection using a questionnaire. The statistical test used in this study was Chi-square with 0.05. The results of this study indicate that the duration of gadget use shows that there is a relationship between the duration of using gadgets and emotional intelligence in SMA Negeri 1 Binjai, Langkat Regency (p=0.02; p<0.05) with a prevalence ratio of 2.78. From the results of the study, parents must be more selective in giving rules for teenagers to play gadgets, namely by frequently monitoring the content seen by teenagers whether it is in accordance with their age and providing rules for the time limit for teenagers to play gadgets so that teenagers do not lose track of time in the sense that teenagers do not neglecting bedtime or bathing, schoolwork, and ignoring the people around the teenager.